Digital Technology in Forced Displacement Settings : Middle East and North Africa Case Studies - Carrette, Sheila; Hasumi, Takahiro (World Bank, Washington, DC, 2019)
A wide range of new technologies are progressively being used for data collection, project planning, implementation, and monitoring and evaluation in forced displacement contexts. This note highlights case studies from countries in the Middle East and North Africa Region and provides practitioners with specific examples of technology use.